THE SOCIAL AND ECONOMIC DIMENSIONS OF THE COVENANT OF THE PROPHET’S (PBUH) STATE IN MADINA - Aeid Abd Ayoub Hameed, Prof. Dr. Zaman Obaid Wannas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Messenger was able to face the internal danger and block the way for those trying to hit them internally by legislating the regime of the brothers. The Quraysh is the archenemy of the Muslims when it was unable to penetrate the first blocking wall, theAnsar, it must move towards the other spectrums of civil society, for society is made up of Muslims and other monotheists, especially the Jews, then idols were worshiped, and this matter was not far from the perceptions of the Prophet Muhammad, may God bless him and his family,so he sought calmly and wisely to conclude a pact (1) between the various components of society, this great achievement has been achieved, which is regarded as a law that applies to all parties that abided by and agreed to it.